Methodology recommendation for one‐criterion transportation problems: Cakmak method - Çakmak, Tanyel; Ersöz, Filiz (Transport, 2007)
Transportation problems (TP) are one of the most prominent fields of application of the mathematical disciplines to optimization and operations research. In general, there are three starting basic feasible solution methods: Northwest Corner, Least Cost Method, VAM – Vogel's Approximation Method. The three methods differ in the quality of the starting basic solution. In this study, we actually show a new method for starting basic feasible solution to one‐criterion‐transportation problems: Çakmak Method. This method can be used for balanced or unbalanced one‐criterion transportation problems, and gives the basic feasible optimum solution accordingly.First Published Online: 27 Oct 2010